Milly, Molly and Blind Bertie - Pittar, Gill; Morrell, Cris (MM House Pub. Gisborne, N.Z., 2003)
Blind Bertie teaches Milly and Molly how to find peace and joy in the simple things of everyday life. Includes teaching guide. Suggested level: junior